2023
DOI: 10.1111/modl.12821
|View full text |Cite
|
Sign up to set email alerts
|

Decoding EFL learners’ internalization of English modal verbs in concept‐based language instruction: Integrating SCOBAs with languaging

Abstract: Concept-based language instruction (C-BLI) is a pedagogy guided by sociocultural theory, which has been shown to be effective in facilitating second language learning. Typical activities include materialization by using a schema for a complete orienting basis of an action (SCOBA) and languaging, through which learners' internalization of scientific knowledge can be observed. However, previous studies have mainly used languaging as an assessment tool to examine the outcome of the internalization of concepts. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Through the analysis of the 23 included empirical studies (i.e. [ 53 , 54 ]), the ways of integrating languaging into L2 classes could be roughly divided into three types ( Table 7 ): experiment, pedagogical means, and mixed integration of experimental and pedagogical techniques. The experimental method of languaging integration ( N = 6) refers to directly leading students to perform languaging activities and analysing their language levels before and after the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Through the analysis of the 23 included empirical studies (i.e. [ 53 , 54 ]), the ways of integrating languaging into L2 classes could be roughly divided into three types ( Table 7 ): experiment, pedagogical means, and mixed integration of experimental and pedagogical techniques. The experimental method of languaging integration ( N = 6) refers to directly leading students to perform languaging activities and analysing their language levels before and after the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Another notable feature of CLII is the implicit teaching mode used to teach knowledge of language rules such as grammar and vocabulary [ 48 , 55 ]. Using languaging activities and following sociocultural theory, Qin et al [ 54 ] investigated the internalisation of content concept and language rule knowledge by students in the CLII model. It was found that CLII was helpful for students’ internalisation of content and language knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the contributions to the special issue directly address C‐BLI, and a fourth focuses more narrowly on the languaging process. Qin, Ouyang, and Ren (2023, this issue) report on a project aimed at teaching the pragmatics of English modal verbs, the first such attempt within the framework of SCT and Gal'perin's (1969) model. In addition to assessing the effects of C‐BLI on learning this feature of English, they also compared written with spoken languaging and what each can tell us about its contribution to the internalization process.…”
Section: Overview Of the Special Issuementioning
confidence: 99%